2010
DOI: 10.1177/1938965510381050
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Future Delinquency for Hotel CMBS Loans

Abstract: The hotel industry seems to be recovering from its recent abyss, but the financial damage to many properties from many months of decline will continue for some time. In particular, the hotel industry faces the prospect of heavily leveraged properties submerged by delinquencies and defaults. An analysis of debt coverage ratios for 365 hotel properties with commercial mortgage-backed security loans shows considerable deterioration from 2008 to a nadir in 2010. Starting in 2011, net operating income and debt cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although their findings indicate an association between the level of distress and the likelihood of resolving a loan, the study was conducted well before the financial crisis. Corgel and Walls (2010) estimate the NOI, DCR, and debt service payments as indicators of loan delinquency in a dataset of 365 hotel CMBS loans in the aftermath of the financial crisis. The results of their analysis reveal hotel loan delinquencies reaching a peak in 2010 and improving NOI growth by 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although their findings indicate an association between the level of distress and the likelihood of resolving a loan, the study was conducted well before the financial crisis. Corgel and Walls (2010) estimate the NOI, DCR, and debt service payments as indicators of loan delinquency in a dataset of 365 hotel CMBS loans in the aftermath of the financial crisis. The results of their analysis reveal hotel loan delinquencies reaching a peak in 2010 and improving NOI growth by 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings reveal the level of distress is associated with a lower likelihood of resolving a loan. In another study, Corgel and Walls (2010) estimate the NOI, DSCR, and debt service payments using a sample of hotels to determine the future delinquency of lodging CMBS loans. While Corgel and Walls's (2010) study is limited by sample size, Quan and Lebret's (2006) research is conducted using data prior to 2004, well before the GFC.…”
Section: Hospitality Commercial Mortgage Researchmentioning
confidence: 99%
“…Their findings revealed that the level of distress was associated with a lower likelihood of resolving a loan. In another study, Corgel and Walls (2010) analyzed a sample of 365 hotels to determine the future delinquency of hotel CMBS loans. The analysis involved estimating NOI, DCRs, and debt service payments as the primary indicators of loan delinquency.…”
Section: Hospitality-related Researchmentioning
confidence: 99%
“…The analysis involved estimating NOI, DCRs, and debt service payments as the primary indicators of loan delinquency. Corgel and Walls (2010) concluded that deterioration in hotel DCRs would reach a peak in 2010 before gradually improving in 2011. Although Corgel and Walls's (2010) study was limited by sample size, Quan and Lebret's (2006) research was conducted using data prior to 2004, well before the current financial crisis of 2008-2009. A few hospitality studies have examined the predictors of hotel values using non-distressed hotel transaction prices.…”
Section: Hospitality-related Researchmentioning
confidence: 99%